Recent environmental change in the Kosterhavet National Park marine protected area as reflected by hydrography and sediment proxy data. (April 2021) - Polovodova Asteman, Irina; Van Nieuwenhove, Nicolas; Andersen, Thorbjørn Joest; Linders, Torsten; Nordberg, Kjell
Abstract: The Koster Trench is the deepest part of the Kosterfjord (Skagerrak, North Sea), which stretches southward along the west coast of Sweden. Since 2009 Kosterfjord has been included in the Marine Protected Area Kosterhavet National Park . To effectively manage national parks, long-term time series of ecological data are needed and those can be derived from local sediment archives. In this study we present multiproxy geochemical (bulk TOC, C/N and heavy metals) and micropaleontological (dinoflagellate cysts, selected palynomorphs and benthic foraminifera) data from a sediment core taken in the southern part of the Koster Trench. Radiometric dating by 210 Pb and 137 Cs shows that the core archived the environmental changes that took place between 1988 and 2012. The TOC, heavy metals and foraminiferal indices indicate mainly high to good Ecological Quality Status, with moderate ecological quality for arsenic concentrations. Dinoflagellate cysts suggest a major change occurring in the upper water column around 2002. The cysts of Pentapharsodinium dalei peak around 1992 and show overall slightly higher relative abundances between 1988 and 2002. Increased abundance of Biecheleria baltica cysts, heterotrophic species, oligotrichids, pollen and spores characterise the upper core part deposited from 2002 to 2012. Also, there is a clear increase of Alexandrium cysts in the top of the core ( 2008–2012). Benthic foraminifera show a major faunal change reflected in a significant increase of agglutinated species (mainly Textularia earlandi ) from 2007 towards present day, while the lower part of the core (1988–2007) is dominated by calcareous species. Overall, the changes demonstrated by the dataset suggest an increased freshwater input or a higher river/land runoff, as supported by climatic and hydrographical data showing increased precipitation over the study area, decreasing salinity, and an increasing trend in particulate organic carbon in the surface waters. These changes, in combination with trawling activities, which have been moved to the deepest part of the trench since 2009, seem to favour dinoflagellate and benthic foraminiferal species with mixotrophic and omnivorous feeding strategies. Similar to the dinocysts, calculated foram-AMBI and NQIforam indices show a shift around 2002 suggesting that environmental changes occurring in the study area are likely linked to darkening of coastal waters. Highlights: Sediment core from the Kosterhavet national park spanning 1988-2012 was studied for sediment geochemistryand microfossils. Dinoflagellate cysts suggest a major change 2002 with decline of P. dalei and increase of Biecheleria baltica. Benthic foraminifera show a in a significant increase of agglutinated species from 2007. Proxy data suggest an increased freshwater input or a higher land runoff, as supported by climatic & hydrographical data.